An operational distinction between quantum entanglement and classical non-separability - Korolkova, Natalia; Sánchez-Soto, Luis; Leuchs, Gerd (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2024)
Quantum entanglement describes superposition states in multi-dimensional systems - at least two partite - which cannot be factorized and are thus non-separable. Non-separable states also exist in classical theories involving vector spaces. In both cases, it is possible to violate a Bell-like inequality. This has led to controversial discussions, which we resolve by identifying an operational distinction between the classical and quantum cases. This article is part of the theme issue 'The quantum theory of light'.
CRIS-Team Scopus Importer:2025-02-04
Keywords: classical entanglement; non-separability; quantum entanglement; quantum measurement